Evolution of Labrador Sea–Baffin Bay: Plate or Plume Processes? - Peace, Alexander; Foulger, Gillian; Schiffer, Christian; McCaffrey, Ken (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
Breakup between Greenland and Canada resulted in oceanic spreading in the Labrador Sea and Baffin Bay. These ocean basins are connected through the Davis Strait, a bathymetric high comprising primarily continental lithosphere, and the focus of the West Greenland Tertiary volcanic province. It has been suggested that a mantle plume facilitated this breakup and generated the associated magmatism. Plume-driven breakup predicts that the earliest, most extensive rifting, magmatism and initial seafloor spreading starts in the same locality, where the postulated plume impinged. Observations from the Labrador Sea–Baffin Bay area do not accord with these predictions. Thus, the plume hypothesis is not confirmed at this locality unless major ad hoc variants are accepted. A model that fits the observations better involves a thick continental lithospheric keel of orogenic origin beneath the Davis Strait that blocked the northward-propagating Labrador Sea rift resulting in locally enhanced magmatism. The Davis Strait lithosphere was thicker and more resilient to rifting because the adjacent Paleoproterozoic Nagssugtoqidian and Torngat orogenic belts contain structures unfavourably orientated with respect to the extensional stress field at the time.